Enhancing student character through collaborative learning: a qualitative study on the contribution of university students at SMP Muhammadiyah Pangsid - Abd Kahar; Isumarni Isumarni; Nurlaelah Nurlaelah; Suhartini Khalik; Sam Hermansyah; Usman M (Edumaspul: Jurnal Pendidikan, 2025)
This study explores how collaborative learning activities facilitated by university students contribute to the development of student character at SMP Muhammadiyah Pangsid. Character education has become an essential component of Indonesia’s educational goals, emphasizing values such as responsibility, cooperation, discipline, and respect. However, schools often face challenges in implementing character-building programs effectively, particularly when learning environments rely heavily on teacher-centered instruction. Using a qualitative descriptive design, this research investigates the role of university students assisting in the school’s learning process and how their involvement supports character formation among junior high school students. Data were collected through classroom observations, semi-structured interviews with teachers and university student assistants, and documentation of classroom activities. The findings show that collaborative learning strategies introduced by university students—such as group problem-solving, peer discussion, and project-based tasks—significantly encouraged students to practice teamwork, communication, empathy, and mutual respect. These interactions created a more supportive and participatory classroom environment, allowing students to engage more actively and develop positive behaviors. Teachers indicated that the presence of university students also enhanced students’ motivation and provided additional role models who reinforced character values through daily classroom engagement. Overall, the study demonstrates that collaborative learning facilitated through university–school partnerships can strengthen character formation in junior high school learners. The involvement of university students not only enriches instructional practices but also supports the school’s efforts to cultivate essential character traits. This research highlights the importance of experiential, interactive, and community-based approaches in promoting character education in Indonesian schools.